Sabah is a creation of westerners - Daily Express, (KK) (Daily Express (KK), 2012)
PROFESSOR Dr Ranjit Singh and Professor Dr Danny Wong have between them done extensive research into Sabah s history Dr Ranjit a Visiting Professor at Universiti Utara Malaysia and once Professor of History at Universiti Malaya is noted for his work on aspects of the natives of Sabah His input for the Malaysian team was crucial in ensuring victory for Malaysia at the International Court of Justice in the Netherlands when Indonesia laid claim to the islands of Sipadan and Ligitan Dr Danny Wong a Sabahan is Professor of History at Universiti Malaya and has written numerous books on aspects of Sabah's history particularly during the war years. They spoke recently to Special Writer MARY CHIN and Chief Editor JAMES SARDA on contemporary issues concerning Sabah and Malaysia